Research progress in multi-beam selective laser melting - ZENG Qingpeng; FU Guang; REN Zhihao; PENG Qingguo; XIAO Huaqiang; LI Shaobo; ZHANG Zhengwen (Cailiao gongcheng)
As a common additive manufacturing （AM） technology， selective laser melting （SLM） is a great potential manufacturing technology for special-shaped parts，such as porous and thin-walled parts. However， the traditional single beam SLM technology develops slowly due to the problems of lesser forming size and inferior efficiency. On the basis of single-beam SLM， multi-beam selective laser melting （MB-SLM） uses multiple beams and multiple galvanometers to partition scan and perform overlap forming. It greatly improves the forming size and efficiency， perfectly solves the inherent problems of single-beam SLM，and is expected to become an emerging technology to expand the application of metal additive manufacturing. The research progress of multi-beam selective laser melting in forming principle， forming equipment， and formation and control of defects is reviewed. The microstructures and mechanical properties of different alloys manufactured by multi-beam selective laser melting are summarized. Importantly， the main strategies to control defects and mechanical properties are highlighted. Finally， the development trends are forecasted， such as the impact of temporal and spatial difference characteristics between multi-beam on mechanical properties， and the consistency change of process parameters between different regions to reduce defects of formed parts.